The Effective Reduction of Violence Against Doctors Through the Improvement of Medical Humanistic Care - Chen G (Journal of Multidisciplinary Healthcare, 2023)
Guochen Chen School of Criminology, People’s Public Security University of China, Beijing, People’s Republic of ChinaCorrespondence: Guochen Chen, School of Criminology, People’s Public Security University of China, Beijing, People’s Republic of China, Email 20052415@ppsuc.edu.cnAbstract: The lack of medical humanistic care has led to the tension between doctors and patients and frequent incidences of violence against doctors. In the past few years, doctors reported feeling insecure due to the frequent occurrence of killing or maiming doctors. Conditions in medicine are not conducive to China’s medical development and progress. This manuscript suggests that the violence against doctors caused by the tension between doctors and patients mainly stems from the lack of medical humanistic care, the overemphasis on technical rationality, and the lack of knowledge on humanistic care for patients. Therefore, the improvement of medical humanistic care is an effective way to reduce the occurrence of violence against doctors. The manuscript describes the steps to improve medical humanistic care and establish a harmonious relationship between doctors and patients to further reduce violence against doctors, improve the quality of humanistic care of medical staff, re-introduce the medical humanistic spirit by ending the dominance of technical rationality, optimize medical treatment processes, and establish the idea of humanistic care for patients.Keywords: medical humanistic care, doctor-patient relationship, the violence against doctors